Contrastes socioambientais na microbacia do riacho Flamengo, Garanhuns-PE - França, Elaynne Mirele Sabino de (2018)
The interactions between man and nature constitute the geographic environment of analysis, and, due to their relation to each other, it has a positive and negative impact, especially when it occurs within a watershed of high environmental vulnerability. Such a repercussion can be apprehended over time and space through the landscape, which brings together the socio-environmental transformations carried out by anthropic action and by natural forces. The objective of this study was to analyze the evolution of the use of the Earth due to changes in the anthropic interaction with nature and its environmental contradictions in the landscape of the Flamenco Riacho Microbacia (MRF) in Garanhuns-PE. The literature review was used as a methodological and procedural subsidy for theoretical reflection and execution of the procedures related to the subject, with technical support for remote sensing and geoprocessing tools, as well as field activities. The results obtained by the morphometric analysis show that the first order channels predominate and these are responsible for the maintenance of the fluvial and pluvial flow in the water courses; The linearity of the channels presents dendritic, endorheic and meandering characteristics; The sandy constitution showed a medium propensity for floods; Evidenced in the use and occupation of the Earth, degradation of vegetation cover; It triggered erosive processes with the appearance of ravine and gullies; soil compaction by traditional management practices; exposed soil with roads to urban expansion; The expansion of the urbanization process was confirmed by the increase of private permanent households (DPPs), which has contributed to increase socio-environmental problems, inadequate occupation of slopes and permanent preservation area. On the other hand, it was expressed that the evolution of the DPPs is also accompanied by the attendance and expansion of parameters that assure the population socio-environmental and economic quality. It was inferred that the pressures of the anthropic action reflected, in most cases, to reorganize the system due to the vegetal suppression; urbanization is markedly defined in the area of soft and undulating topography with a pleasant aspect, even if in cases where this limit has been exceeded and occupied places of high environmental risk, however, anthropogenic derivations may have triggered extreme circumstances. It was possible to visualize the socio-environmental dynamics that the microbasin is inserted in the recognition of the evolution of the use and occupation of the Earth, in attributes of physical, environmental and socioeconomic character.